Characteristics of dairy cow farms with positive economic results - Gabriela-Dalila Stoica (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The paper presents the analysis of synthetic economic indicators from 2018-2020 for a number of 30 dairy farms in various areas of the country, which were the subject of case studies. The purpose of analyzing the indicators is to know the essence of the elements that contributed to obtaining positive economic results for the dairy farms analyzed. The average size of the analyzed farms is 104.16 heads, being between 5-568.33 heads. The average milk production per cow head was 5709.44 liters, with a minimum of 3100 l / head and a maximum of 9,633, 3 l / head. By capitalizing the milk productions obtained at an average price of 1.69 lei / l, registered for the analyzed farms, an average profit of 0.13 lei / liter was achieved, as well as a profit rate between 0 .09% and 27.25%. Although they registered positive economic results, at the level of all 30 economic entities, there was, on average, an exploitation risk rate of 82.8%. But the diversity of the products obtained, the capitalization of the fodder and their transformation into high quality animal products contribute to the development of the sector from a sustainable point of view.
Keywords: Q10; Q12; 330; indicators; farms; milk; economic